Bridging the gap in outreach and compliance with mass drug administration for lymphatic filariasis elimination in an endemic district in Kerala, India: an intervention research approach. Issue 3 (25th February 2019) - Nandha, B; Meenakshy, V; Abdul Khader, Nazer; Vijayakumar, K N; Jambulingam, P
Abstract: Lymphatic filariasis (LF), a neglected tropical disease is targeted for elimination globally by 2020. National Health Policy of India set the goal by 2017 and annual single-dose mass drug administration (MDA) with anti-filarial drugs is in operation in endemic districts since 2004. Performance and effectiveness of MDA was diverse across the nation and prevalence of infection continues above threshold level in 50% of endemic districts which requires alternative strategies. National programme aims at achieving >65% consumption for transmission control. Post 10 rounds of MDA in an endemic district of Kerala state, a three-arm study identified determinants in gap in outreach and consumption, based on which context-dependent intervention using social group work and networking (SGWN) was implemented and impact assessed. A spill over effect with overall increase in coverage and consumption rates irrespective of arms apparently is due to inclusive improvement in MDA programme whereas, significant relative improvement in intervention arm reflects effectiveness of SGWN strategy. Though reduction in microfilaria prevalence in all arms was observed, it was significant between intervention and comparison arm. This study highlights need for context-dependent communication strategy to improve MDA for accelerating LF elimination by the targeted 2020.